Testing the Effects of Regional, Ethnic, and International Dialects of English on Listening Comprehension - Roy C. Major et al (Language Learning 55:1, March 2005, pp. 37-69, 2005)
It is widely believed that listeners understand some dialects more easily than others, although there is very little research that has rigorously measured the effects. This study investigated whether listeners experience more difficulty with regional, ethnic, and international dialects of English than with Standard American English. The results demonstrated that speaker dialect had a significant effect for both English as a second language (ESL) listeners (n158) and native-Englishspeaking listeners (n58). ESL listeners scored lower on listening comprehension tests hearing ethnic and international dialects of English compared to Standard American English; however, there were no significant differences between the scores of those hearing regional dialect and Standard American English. These results suggest that regional dialects should be considered in listening comprehension tests such as the Test of English as a Foreign Language.